2016
DOI: 10.1186/s13717-016-0054-4
|View full text |Cite
|
Sign up to set email alerts
|

Invasion by Conyza sumatrensis alters soil microbial community structure in urban ecosystems

Abstract: Introduction: Whether invasive plants stimulate or inhibit the soil microbial diversity is still an open question. Despite large-scale invasion by Conyza sumatrensis (Retz.) E. Walker in the urban ecosystems of the Srinagar city of the Kashmir Himalayan region, limited information exists on its impact, particularly, on the belowground microbial diversity. The present study was thus conducted to compare the soil microbial (bacterial and ascomycetous fungal) diversity between the sites invaded by C. sumatrensis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…It is a tall broad-leaved fleabane [ 3 ] and belongs to Asteraceae family. It is broad-leaved, seed-reproducing, annual or biennial, herbaceous species [ 3 , 4 ]. The stem of C .…”
Section: Introductionmentioning
confidence: 99%
“…It is a tall broad-leaved fleabane [ 3 ] and belongs to Asteraceae family. It is broad-leaved, seed-reproducing, annual or biennial, herbaceous species [ 3 , 4 ]. The stem of C .…”
Section: Introductionmentioning
confidence: 99%
“…Sumatran Fleabane (C. sumatrensis) is an annual dicot species belonging to the family Asteraceae, native to Central and South America and is highly invasive in different warm-temperate and tropical areas of the Old World. High invasiveness is promoted by large achene production and extensive seed dispersal [6,23,24]. This species has previously been reported to evolve both TSR and NTSR mechanisms to EPSPS inhibitors [2].…”
Section: Introductionmentioning
confidence: 94%
“…Despite the economic importance of C. sumatrensis, few studies have particularly addressed the traits of this weed species. Only some reproductive (Hao et al 2009) and morphological (Sansom et al 2013) features, the occurrence of biotypes resistant to herbicides (Santos et al 2014a(Santos et al , 2014b(Santos et al , 2015, the impact of invasions on the soil microbiome (Rasool et al 2016), and genetic diversity within and among different biotypes (Marochio et al 2017;Schneider et al 2020) have been reported so far. Genetic diversity analysis of weed populations has practical importance, such as in predicting population response to biological or chemical control (Ward et al 2008).…”
Section: Introductionmentioning
confidence: 99%